Phraseology in linguocognitive perspective - Gutovskaya, Marina S. (Journal of the Belarusian State University. Philology, 2024)
The paper views the historical-scientific prerequisites for the study of complex relations between language and thinking, the formation of cognitive linguistics. The features of the linguocognitive approach to the study of phraseology are discussed, on the example of the English phraseological units with the semantics ‘achieve success’ the logic of the structural and linguocognitive research of phraseology is demonstrated. The objective, general aims and prospectives of cognitive phraseology are formulated.
Keywords: phraseological unit; cognitive linguistics; cognitive phraseology